(untitled) (Cardiovascular Journal, 2011)
Background: Cardiac Scan (MP-SPECT) is a widely utilized noninvasive imaging modality for diagnosis, prognosis, and risk stratification of coronary artery disease. In Bangladesh it is a recently introduced test and there is no study upon it. Considering this ground the study is perform on Bangladeshi patients. Methods: 100 referral patients underwent MPI for evaluation of perfusion status of myocardium. The patients either of suspected IHD or diagnosed case of IHD were referred from different cardiology unit or surgery unit of NICVD. Technetium 99m (99"Tc) isotopes and tetrofosmin used in the same day stress and rest protocol. Result: The commonest findings observed in this present analysis were the early age group patients mostly of female having DCM, but the later age group of patients are of both male and female having Angina Pectoris, OMI and ICM. The referral patients by cardiologists or cardiac surgeons are mostly limited to the pre therapeutic evaluation rather than diagnostic indication. The most common indication is the evaluation of myocardial viability and aim of subsequent treatment. Conclusion: Analysis of perfusion status, decision of subsequent treatment either by medicine or CABG, conform the usually described pattern in western literature. Keywords: Myocardial viability, Cardiac Scan (Synoname: WI, MP-SPECT, Thallium Scan). MPI DOI: http://dx.doi.org/10.3329/cardio.v1i1.8205 Cardiovasc. j. 2008; 1(1) : 53-58